Good governance and the rule of law : newspaper contributions made on behalf of the Citizens' Movement for Good Governance, September 2005-March 2011 - Visvalingam, A. C.; Citizens' Movement for Good Governance (Colombo, Sri Lanka) (Colombo : Citizens' Movement for Good Governance : Distributed by Vijitha Yapa Bookshop, 2011)
With reference to Sri Lanka.
Includes index.
Keywords: Rule of law -- Sri Lanka; Civil rights -- Sri Lanka; Sri Lanka -- Politics and government -- 21st century